The Relationship between Functional Ovarian Cyst and Ovarian Reserve among Infertile Females - Modoodi, Mozhgan; Zare, Maryam; Nikbakht, Roshan; Mirzaei, Maryam; Bazrafkan, Mahshid; Ataei, Mina (International Journal of Psychosocial Rehabilitation, 2019)
Introduction: Functional ovarian cyst is a common phenomenon in women. Ovarian reserve changes with increasing the age or under the effect of ovarian diseases. This age-related reduction in ovarian reserve, especially in women who have lower ovarian reserve due to ovarian diseases, can have a greater impact on the women’s fertility. The present study was conducted to compare the ovarian reserve in the infertile women with and without a functional ovarian cyst by measuring the serum levels of the anti-Müllerian hormone. Materials and Methods: The present study is an analytical study conducted on 60 infertile women referred to the Infertility Research Center of Ahvaz Jundishapur University of Medical Sciences in 2011. Transvaginal sonography was first performed and based on the sonography, the patients were divided into two groups, including a case group (n = 30) with an ovarian cyst and a control group (n = 30) without a ovarian cyst. The blood samples were taken from all patients to measure the serum levels of the anti-Müllerian hormone and the samples were sent to a laboratory (Tohidi Laboratory). After 3 months, transvaginal sonography was re-performed on the patients with cysts to diagnose the cases of persistent cysts or other ovarian cysts. The ovarian reserve was compared between the two groups according to the mean serum levels of the anti-Müllerian hormone. The data were analyzed using SPSS version 17 software. The significance level was considered 0.05. Results: The mean age of the case and control groups was 28.66 and 29.16 years, respectively. Duration of the infertility and the number of people with primary or secondary infertility were not significantly different between the two groups. The mean serum levels of the anti-Müllerian hormone were 2.70 ng / ml in the case group and 2.55 ng / ml in the control group (P = 0.821). Conclusion: Based on the results, the rate of ovarian reserve in the infertile women with and without a physiological ovarian cyst is not different. Further studies with larger sample sizes are recommended to confirm the results of this study.